The contours of inequality: The links between socio-economic status of students and other variables at the University of Johannesburg (Journal of Student Affairs in Africa, 2021)
The low level of student success in South Africa is an intractable problem, with levels of success differing between the various groups that make up South African society. One of the major constraints influencing student success involves the socio-economic status (SES) of newly entering students. In the South African context, with its very high levels of SES inequality and other social stratifications, a better understanding of issues related to SES would allow them to be addressed in targeted ways that lead to improved student success. This study was conducted at the University of Johannesburg and used data collected between 2010 and 2015. In this study, the SES of students was determined by measuring their self-reported Living Standards Measure (LSM) level. The relationships between the SES level and various socio-demographic variables were then tested using the chi-square test with standardised residuals. The trends that emerged can assist institutions to gain a more nuanced understanding of SES and its impact in the South African context. Three clear clusters emerged each with their own distinguishing attributes and risk profiles.
Keywords: Higher education; inequality; social stratification; transformation; University of Johannesburg; South Africa